Prevalence of Achilles and patellar tendinopathy and their association to intratendinous changes in adolescent athletes. Issue 3 (11th September 2014) - Cassel, M.; Baur, H.; Hirschmüller, A.; Carlsohn, A.; Fröhlich, K.; Mayer, F.
<x xml:space="preserve">Abstract</x> Achilles (AT) and patellar tendons (PT) are commonly affected by tendinopathy in adult athletes but prevalence of symptoms and morphological changes in adolescents is unclear. The study aimed to determine prevalence of tendinopathy and intratendinous changes in ATs and PTs of adolescent athletes. A total of 760 adolescent athletes (13.0 ± 1.9 years; 160 ± 13 cm; 50 ± 14 kg) were examined. History, local clinical examination, and longitudinal Doppler ultrasound analysis for both ATs and PTs were performed including identification of intratendinous echoic changes and vascularization. Diagnosis of tendinopathy was complied clinically in case of positive history of tendon pain and tendon pain on palpation. Achilles tendinopathy was diagnosed in 1.8% and patellar tendinopathy in 5.8%. Vascularizations were visible in 3.0% of ATs and 11.4% of PTs, hypoechogenicities in 0.7% and 3.2% as well as hyperechogenicities in 0% and 0.3%, respectively. Vascularizations and hypoechogenicities were statistically significantly more often in males than in females (P ≤ 0.02). Subjects with patellar tendinopathy had higher prevalence of structural intratendinous changes than those without PT symptoms (P ≤ 0.001). In adolescent athletes, patellar tendinopathy is three times more frequent compared with Achilles tendinopathy. Longitudinal studies are necessary to investigate physiological or pathological origin of vascularizations and its predictive value in development of tendinopathy.